2021
DOI: 10.1186/s12985-021-01489-0
|View full text |Cite
|
Sign up to set email alerts
|

False negative rate of COVID-19 PCR testing: a discordant testing analysis

Abstract: Background COVID-19 is diagnosed via detection of SARS-CoV-2 RNA using real time reverse-transcriptase polymerase chain reaction (rtRT-PCR). Performance of many SARS-CoV-2 rtRT-PCR assays is not entirely known due to the lack of a gold standard. We sought to evaluate the false negative rate (FNR) and sensitivity of our laboratory-developed SARS-CoV-2 rtRT-PCR targeting the envelope (E) and RNA-dependent RNA-polymerase (RdRp) genes. Methods SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
153
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(171 citation statements)
references
References 26 publications
2
153
1
2
Order By: Relevance
“…Our data analysis is concordant with other studies reporting false-negative results from RT-PCR tests ranging up to 30% [4]. Several studies have already showed that the diagnostic efficacy between RT-PCR test kits for SARS-CoV-2 nucleic acid detection may differ significantly depending on the probes and primers used [12,13].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data analysis is concordant with other studies reporting false-negative results from RT-PCR tests ranging up to 30% [4]. Several studies have already showed that the diagnostic efficacy between RT-PCR test kits for SARS-CoV-2 nucleic acid detection may differ significantly depending on the probes and primers used [12,13].…”
Section: Discussionsupporting
confidence: 92%
“…According to the WHO and Chinese Center for Disease Control and Prevention (CDC), real-time PCR (RT-PCR) is considered the 'gold standard' method for detection of SARS-CoV-2 infection [3]. Nevertheless, studies have shown that RT-PCR is an error-prone method showing false-negative results rates from respiratory samples for SARS-CoV-2 ranging from 1% to 30% [4]. These diagnostic errors are related to a number of preanalytical and analytical factors, including the source of the sample, delays or inadequate storage conditions before arrival to the laboratory, possible errors of RNA extractions, as well as the different quality and sensitivity of detection kits [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…46, 48, 51, 54, 55 While three studies on hospital-based testing mentioning the interval to reassessment 57, 58, 63 showed no such linearity between reassessment interval and false negative rate (Figure 6C, Table 6), repeat RT-PCR testing of nasal swabs after a median interval of 7.5 days reported detection of highest fraction of initial false negative RT-PCR results. 58 Plot of RTPCR false negative detection on reassessment against adjusted interval between initial RT-PCR and reassessment combining population-based screening 42-44 and symptom-based testing studies 46, 48, 51, 54, 55 showed a peak between 7-8 days. It should be noted that although desirable, the interval between symptom onset and initial RT-…”
Section: Resultsmentioning
confidence: 99%
“…After the initial phase of this pandemic, in fact, some author argued for low sensitivity of RT-PCR performed on NPS [2], suggesting that repeating the test, or using other samples, may reduce the number of false negatives [4], which another study estimated to be as high as 9.3% [5]; noteworthy, other reports found even lower sensitivity for NPS [6,7]. Beyond these data, the overarching question still remains unsolved: how much can we rely on a single negative NPS to rule out COVID-19, if clinical suspicion remains high?…”
mentioning
confidence: 99%